Supplementation of Cassava Leaf (Manihot Esculenta Crantz) in Field Grass in Sheep Growth - Andhika Putra; Wawan Setiawan Sinaga (Talenta Publisher, 2018)
Supplementation of cassava leaves (ManihotesculentaCrantz) in the base grass field ration of male rams in the growth period aims to determine the effect of giving cassava leaves to the performance of sheepparameters measured in this study were consumption level, body weight gain and feed conversion in local sheep in the growth period. This study used randomized complete design (CRD) 4 treatments and 6 replications. Using male local sheep with an average body weight of = 12 ± 1.93. The treatment used T0 = without giving cassava leaves (Control), T1 = 25% cassava leaves, T2 = 50% cassava leaves, T3 = 75% cassava leaves. The results of the study with variance analysis showed no significant effect (p> 0.05)feed consumption level, body weight gain and feed conversion ratio the conclusion of this study is the supplementation of cassava leaves (ManihotesculentaCrantz) on grass-based rations did not provide a different growth increase in weaning local male sheep.